Management control system in an outsourced solid waste management in Malaysia - Che Pak, Nur Azliani; Abdullah, Shamsul Nahar; Ismail, Suhaiza; Mohd Alwi, Norhayati (The Institute for Strategic and Sustainable Accounting Development (ISSAD), 2016)
The focus of current business environment has changed to alliances, hence, it is important to have an appropriate governance structure or a good management control system. Thus, this conceptual paper discuss the development of management control system and the outsourcing process of solid waste management in Malaysia. Solid waste management is one of the important services provided by Malaysian government. Due to many negative feedbacks received for the solid waste management services provided by local governments, the Malaysian government decided to outsource it to private vendors since 1996. After the outsourcing process comes into action, many parties involved in managing it. To name a few, it involved National Solid Waste Management Department (JPSPN), SWCorp, private vendors and local governments. Thus, in order to align the objectives of all parties involved, management control system emerge as one of the important and significant tools.